The role of intersection topography in bond selectivity of cis-trans photoisomerization - Ben-Nun, M. (The National Academy of Sciences, 2002)
Ab initio methods are used to characterize the ground and first excited state of the chromophore in the rhodopsin family of proteins: retinal protonated Schiff base. Retinal protonated Schiff base has five double bonds capable of undergoing isomerization. Upon absorption of light, the chromophore isomerizes and the character of the photoproducts (e.g., 13-cis and 11-cis) depends on the environment, protein vs. solution. Our ab initio calculations show that, in the absence of any specific interactions with the environment (e.g., discrete ordered charges in a protein), energetic considerations cannot explain the observed bond selectivity. We instead attribute the origin of bond selectivity to the shape (topography) of the potential energy surfaces in the vicinity of points of true degeneracy (conical intersections) between the ground and first excited electronic states. This provides a molecular example where a competition between two distinct but nearly isoenergetic photochemical reaction pathways is resolved by a topographical difference between two conical intersections.